2015
DOI: 10.1021/acs.jpca.5b07873
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Vibrations as Promoters of Chemical Reactivity on Metal Surfaces

Abstract: Studies exploring how vibrational energy (Evib) promotes chemical reactivity most often focus on molecular reagents, leaving the role of substrate atom motion in heterogeneous interfacial chemistry underexplored. This combined theoretical and experimental study of methane dissociation on Ni(111) shows that lattice atom motion modulates the reaction barrier height during each surface atom's vibrational period, which leads to a strong variation in the reaction probability (S0) with surface temperature (Tsurf). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 48 publications
2
43
0
Order By: Relevance
“…For the laser-off measurements, the sticking coefficient for T S = 500 K is lower for E trans less than 90 kJ/mol, whereas increasing T S at higher energies does not change S laser-off 0 significantly. This is consistent with previous experiments performed by Utz et al for the dissociative chemisorption of CH 4 on Ni(111), 22,25 where it was found that S ν 3 0 increased more as T S was increased when the total energy (E trans + E vib ) was lower than the barrier height, and S ν 3 0 changed less when the total energy was greater than the barrier height.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For the laser-off measurements, the sticking coefficient for T S = 500 K is lower for E trans less than 90 kJ/mol, whereas increasing T S at higher energies does not change S laser-off 0 significantly. This is consistent with previous experiments performed by Utz et al for the dissociative chemisorption of CH 4 on Ni(111), 22,25 where it was found that S ν 3 0 increased more as T S was increased when the total energy (E trans + E vib ) was lower than the barrier height, and S ν 3 0 changed less when the total energy was greater than the barrier height.…”
Section: Resultssupporting
confidence: 93%
“…First principles theory combined with classical and quantum dynamics simulations is able to reproduce at least qualitatively many of the experimental observations. [15][16][17][18][19][20][21][22] Several techniques have been developed to measure sticking coefficients with quantum state resolution, for example, by detecting the surface bound products using Auger electron spectroscopy, 5,6,23,24 reflection absorption infrared spectroscopy, 7,11,15,21 or titration of the adsorbates to make molecules that desorb and can be detected in the gas phase mass spectrometrically. 9,12,22,25 Whilst these have proved to be powerful techniques for determining quantum state resolved sticking coefficients, they share a common disadvantage in that calibrations are necessary to quantify the adsorbate coverage and number of molecules incident on the surface, both of which need to be known to accurately determine the sticking coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Note that a purely vibrationally adiabatic model predicts that molecules in the ν 3 state are about as reactive as those in the ground state. In fact, experiment, like our theory, finds a strong vibrational enhancement; 25,46,47 the ν 1 enhancement is simply larger.…”
Section: B Theory: Reaction Path Hamiltonian (Rph) Model For Methanesupporting
confidence: 70%
“…At a surface temperature of 150 K and at lower incident energies, the branching ratio for the dissociation of CHD 3 , CH 2 D 2 , and CH 3 D on Pt(111) has been shown to be statistical under laser-off conditions, 49 whereas when a quantum of C–H stretch was added to the molecule, only C–H cleavage was observed. 49,50 Increasing the surface temperature (to 650 K) lowers the effective activation barrier to the dissociative chemisorption due to the thermal motion of the atoms in the surface, 14,51,52 which when combined with a higher incident translational energy is likely to make CHD 3 dissociation less bond selective for υ 1 = 1, as is seen to be the case in the AIMD calculations.…”
Section: Results and Discussionmentioning
confidence: 76%